STUDI KONSENTRASI CO AKIBAT KENDARAAN BERMOTOR DI KAWASAN PASAR TRADISIONAL KOTA PADANG - Vera Surtia Bachtiar; Vivin Alfirna (Jurnal Dampak, 2017)
The traditional market area in Padang City is an area with a fairly high transportation activity of motor vehicles. The aims of this study is to determine the air quality for CO parameter due to motor vehicles in Padang City. The measurement of CO concentration was conducted in the traditional markets in Padang City which were located near the highway, namely Bandar Bandar Market, Pasar Raya Padang Market and Lubuk Buaya Market to see the effect of motor vehicle on transportation activity. CO measurements were carried out using CO meters for one hour during peak hours (07.00-08.00, except for Pasar Raya Market, conducted at 16.00-17.00) and off-peak hours (10.00-11.00 wib). CO concentrations during peak hours range between 5.92 and 11.67 ppm, while in the off-peak hours between 4.58 and 9.25 ppm. The outside of the traditional market (8.50-11.67 ppm) which is located on the edge of the highway, has a higher CO concentration than the inside (4.58-5.92 ppm). The measured CO concentrations in each location are below the national air quality standards. It means, the presence of traffic flow in the traditional market area in Padang City affects air quality on the edge of the highway, but not so affect the air quality in the inside area in the traditional market.Keywords: Transportation, Motor Vehicle, CO Concentration, Traditional Market.ABSTRAKKawasan pasar tradisional Kota Padang merupakan kawasan dengan aktivitas transportasi kendaraan bermotor yang cukup tinggi. Penelitian ini bertujuan untuk mengetahui kualitas udara untuk parameter CO akibat kendaraan bermotor di Kota Padang. Pengukuran konsentrasi CO dilakukan di pasar tradisional di Kota Padang yang berada dekat jalan raya, yaitu Pasar Bandar Buat, Pasar Raya Padang dan Pasar Lubuk Buaya untuk melihat pengaruhnya dari aktivitas transportasi kendaraan bermotor. Pengukuran CO dilakukan menggunakan CO meter selama satu jam pada jam sibuk (07.00-08.00 wib, kecuali untuk Pasar raya Padang, dilakukan pukul 16.00-17.00 wib) dan jam senggang (10.00-11.00 wib). Konsentrasi CO saat jam sibuk berkisar 5,92–11,67 ppm, sedangkan pada jam senggang sebesar 4,58 – 9,25 ppm. Bagian luar pasar tradisional (8,50–11,67 ppm) memiliki konsentrasi CO lebih tinggi dari pada bagian dalamnya (4,58-5,92 ppm). Konsentrasi CO terukur di setiap lokasi masih berada di bawah baku mutu. Artinya, adanya arus lalu lintas di kawasan pasar tradisional di Kota Padang mempengaruhi kualitas udara pada pinggir jalan raya, tetapi tidak begitu mempengaruhi kualitas udara di kawasan dalam pasar tradisonal tersebut.Kata kunci: Transportasi, Kendaraan Bermotor, Konsentrasi CO, Pasar tradisional.